Use of zeolites for decontamination of radioactively contamined working surfaces - Lonin, A.Y.; Krasnopyorova, A.P. (Вопросы атомной науки и техники, 2007)
The possibility of using zeolites in decontaminants applied for cleaning up radioactively contaminated working clothes and surfaces is studied. It has been established that zeolites can be used for decontamination of working clothes, as well as, working surfaces presented by metals, ceramic tile, wood coated with paint or varnish, glass. The data on different zeolite-based decontaminant in comparison with a known detergent ”Zashchita” are given. Досліджено можливість використання цеолітів у засобах для дезактивації спецодягу, робочих поверхонь. Встановлено, що цеоліти можуть бути використані для дезактивації спецодягу, а також робочих поверхонь представлених - металом, керамічною плиткою, деревом покритим фарбою або лаком, склом. Наведені порівняльні дані різних складів на основі цеолітів з відомим дезоктивуючим засобом "Захист". Исследована возможность использования цеолитов в средствах дезактивации спецодежды, рабочих поверхностей. Установлено, что цеолиты могут быть использованы для дезактивации спецодежды, а также рабочих поверхностей представленных - металлом, керамической плиткой, деревом покрытым краской или лаком, стеклом. Приведены сравнительные данные различных составов на основе цеолитов с известным дезактивирующим средством "Защита".